2019
DOI: 10.1186/s12885-018-5148-1
|View full text |Cite
|
Sign up to set email alerts
|

Free testosterone value before radical prostatectomy is related to oncologic outcomes and post-operative erectile function

Abstract: PurposeTo investigate whether free testosterone (FT) prior to radical prostatectomy was related to post-operative oncologic outcomes, erectile function and continence.MethodsThe data of 586 patients with available information underwent treatment in our center was retrospectively reviewed. Total testosterone (TT) was tested by chemiluminescence immunoassay, and FT value was calculated using Vermeulen’s formula. Post-operative continence and erectile function were evaluated by the requirement of pad and the IIEF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
4
1
Order By: Relevance
“…Martinez-Jabaloyas et al (23) found that the total testosterone (TT) levels were not related to sexual function in men with ED. And it has been reported that free testosterone (FT) has a predictive effect on the occurrence of ED after radical prostatectomy (15). Our study found that comparison between groups in CP/CPPS patients were not statistically significant (P>0.05).…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Martinez-Jabaloyas et al (23) found that the total testosterone (TT) levels were not related to sexual function in men with ED. And it has been reported that free testosterone (FT) has a predictive effect on the occurrence of ED after radical prostatectomy (15). Our study found that comparison between groups in CP/CPPS patients were not statistically significant (P>0.05).…”
Section: Discussioncontrasting
confidence: 60%
“…( 14) . For example, free testosterone is one of the predictors of ED occurrence (15). However, there is still a lack of clinical investigations for CP/CPPS patients with ED, especially the relationship between various serum hormones and ED.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research on low testosterone and surgical outcomes in the urologic literature has primarily focused on prostate cancer (PCa) and radical prostatectomy (RP) patients. Among RP patients, low testosterone has been shown to increase upgrading and upstaging at the time of surgery, delay time to return of urinary control, and increase risk of postoperative erectile dysfunction 18–20 . However, in our RN cohort, hypogonadism was associated with outcomes more commonly seen in the general population.…”
Section: Discussionmentioning
confidence: 62%
“…Among RP patients, low testosterone has been shown to increase upgrading and upstaging at the time of surgery, delay time to return of urinary control, and increase risk of postoperative erectile dysfunction. [18][19][20] However, in our RN cohort, hypogonadism was associated with outcomes more commonly seen in the general population. For example, low testosterone is a well-established risk factor for cardiovascular disease with multiple prior studies showing an increased risk of atherosclerosis, coronary artery disease, and major adverse cardiovascular events (MACEs).…”
Section: Discussionmentioning
confidence: 83%
“…In addition, Wang et al [24] showed that patients with an annual testosterone reduction of more than 30 ng/dL had a nearly 5-fold increase in PCA risk. Moreover, recent evidence in the literature has demonstrated that low baseline serum levels of free testosterone are associated with an increased risk of high-grade PCA [25] as well as adverse pathologic features, functional outcomes, and biochemical recurrence [26].…”
Section: Discussionmentioning
confidence: 99%